Effect of temperature fluctuation during frozen storage on beef quality. Issue 1 (8th November 2020) - Deng, Shaolin; Han, Yiqing; Gao, Tingxuan; Ye, Keping; Liu, Jia
Abstract: This study investigated the effects of fluctuating temperature on the quality of frozen beef, which were preserved under three different temperature fluctuation ranges (wide temperature fluctuation −18 ± 2°C, medium temperature fluctuation −18 ± 1°C, and small temperature fluctuation −18 ± 0.5°C). Results showed that, with an increase of in small temperature fluctuation, the rate of thaw loss significantly increased, total volatile basic nitrogen value increased. However, these temperature fluctuations did not influence the beef color, TBARS value, and muscle fiber diameter. This indicated that, under a certain level, smaller temperature fluctuation had better preservation on frozen beef. Practical applications: This research provide a theoretical basis for reducing the effects of temperature fluctuation on the quality of frozen beef preserved in domestic freezers and small temperature fluctuation can be applied to the development of intelligent defrosts.